Environmental Sanitation And Dengue Hemorrhagic Fever - Marlinang I Silalahi; Tonggo Apriliani (Akupun Tour Publisher, 2022)
Background: Dengue hemorrhagic fever (DHF) is a disease caused by the dengue virus which belongs to the arthropod borne virus. DHF is transmitted through mosquitobites from the genus Aedes. This disease is related to environmental conditions and community behavior. Purpose: The purpose of this study is to determine the relationship of enviroment sanitation to the incident of DHF in Martubung Village,Medan Labuhan subdisctrict. Method: This type of study is an analytical survey with across sectional method. The variables used in this study are waterreservoirs, landfills, and wastewater drain. There are 122 respondents in this research. Data collection using observation sheets and data analysis methods using Chi-square with a significance level of 0.05. Result: The results of data analysis showed that there was a relationship between water reservoirs (p=0,025), landfills (p=0,023) and wastewater (p=0,01) with the incidence of DHF in the Martubung Village, Medan Labuhan subdisctrict. Conclusion: It is better for each respondent to be more concerned to always maintain a healthy condition of home environment sanitation, it is necessary to carry out routine cleaning as well as mutual cooperation activities to clean the environment.